2019
DOI: 10.2147/ijn.s216365
|View full text |Cite
|
Sign up to set email alerts
|

<p>Poly (lactic-co-glycolic acid)/graphene oxide composites combined with electrical stimulation in wound healing: preparation and characterization</p>

Abstract: In this study, we fabricated multifunctional, electrically conductive composites by incorporating graphene oxide (GO) into a poly (lactic-co-glycolic acid) (PLGA) copolymer for wound repair. Furthermore, the resultant composites were coupled with electrical stimulation to further improve the therapeutic effect of wound repair. Methods: We evaluated the surface morphology of the composites, as well as their physical properties, cytotoxicity, and antibacterial activity, along with the combined effects of composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…In our previous study, PLGA material was demonstrated to have no obvious antibacterial activity, thus, PLGA was used as the experimental control group. 49 As shown in Figure 6A , the PDA@PLGA group showed a similar OD value as the PLGA group, indicating that the PDA coating had no obvious effect on the antibacterial properties of the material. After loading AuNPs on the surface of the PLGA scaffolds, the OD value of bacterial solutions decreased to a certain extent, but the decreasing trend was not obvious, and a significant difference was found only when scaffold was co-culture with E coli (P < 0.05).…”
Section: Resultsmentioning
confidence: 76%
“…In our previous study, PLGA material was demonstrated to have no obvious antibacterial activity, thus, PLGA was used as the experimental control group. 49 As shown in Figure 6A , the PDA@PLGA group showed a similar OD value as the PLGA group, indicating that the PDA coating had no obvious effect on the antibacterial properties of the material. After loading AuNPs on the surface of the PLGA scaffolds, the OD value of bacterial solutions decreased to a certain extent, but the decreasing trend was not obvious, and a significant difference was found only when scaffold was co-culture with E coli (P < 0.05).…”
Section: Resultsmentioning
confidence: 76%
“…[ 111 ] Under external ES, the scaffold dressing exhibits high bioactivity, supporting myoblast adhesion and strengthening cell responses, further enhancing wound healing ( Table 5 ). [ 110,112–123 ] Another series of conductive hydrogels that are based on dopamine‐grafted hyaluronic acid and polydopamine‐coated reduced graphene oxide (rGO), which are crosslinked by oxidative coupling of catechol groups using an H 2 O 2 /horseradish peroxidase catalytic system, have been prepared as materials for dressing wounds (Figure 6b). [ 115 ] The as‐prepared composite hydrogels have adhesive, hemostatic, and antioxidant properties as well as mechanical properties that are similar to those of human skin.…”
Section: Electroactive Wound Dressings That Incorporate Inorganic Conmentioning
confidence: 99%
“…There are many more studies on functional wound dressings. Considering in vivo studies after 2019, electrically conductive dressings containing graphene oxide (GO), 244 polypyrrole, 245,246 MXene, 247 and liquid metal integrated with a microneedle patch 248 succeeded in accelerating wound healing with external electrical stimulation. In addition, the application of conductive dressings carrying GO, 249–252 carbon nanotubes, 253,254 polypyrrole, 255 and polyaniline 256 to the skin has been reported to enhance wound healing in vivo in the absence of external stimulation, such as application of heat or antibiotics.…”
Section: Skin Devices Based On the Electrical Features Of The Skinmentioning
confidence: 99%